Educating and Enlightening: A Portrait of the Muhammadiyah Social Movement in Wolo during the Old Order (Mendidik dan Mencerahkan: Potret Gerakan Sosial Muhammadiyah di Wolo pada Masa Orde Lama) - Moh. Yahya Obaid; Rosmini Rosmini; Rizal Rizal (Shautut Tarbiyah, 2022)
This study aims to analyze the history of Muhammadiyah's contact with Wolo District, its existence and political dynamics, and its social pattern of Da'wah during the Old Order period. The study design is ex post facto research. Data were obtained through documents, interviews and observations, and were analyzed by heuristics, source criticism, interpretation, and historiography. The results of this study indicate that since 1957 Wolo has become a branch of the Kolaka Regency Muhammadiyah and experienced rapid development after the arrival of immigrants from the Waru Ponre, Bone Regency. During the old order, Muhammadiyah Wolo experienced a period of contamination with the DI-TII movement, politically channeling its aspirations to Masyumi and opposing the ruling political ideology (PNI) which synergized with the PKI. The social pattern of Dakwah Muhammadiyah Wolo in rectifying the religion of the ummah during the Old Order era used 5 (five) approaches namely: indoctrination, moral reasoning, forecasting consequences, value clarification, as well as ibrah and amtsal. In addition to the five approaches, four internalization strategies are also applied, namely: exemplary strategy, problem/case analysis, instilling contextual educational values, and strengthening values. The social fact of da'wah is manifested by charitable efforts in the fields of education, health and socio-economics.Keywords:     Educate, Enlighten, Social Movement, Muhammadiyah, Old Order